Digital Signal Processing Over Analog Signal Processing - Sharma, Sushma; Kumar, Hitesh; Thareja, Charul (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2014)
This paper provides a survey of digital signal processing over analog signal processing. Initially digital signal processing is developed to replace limited application based analog signal processing (ASP) of high cost. This paper describes the comparison of analog signal processing (ASP) and digital signal processing, technology under digital signal processing , application of digital signal processing, new technology of digital signal processing (DSP). This paper also focuses on the future scope of digital signal processing (DSP).